2020
DOI: 10.1186/s12877-020-1493-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of dementia and attitude towards prevention: a qualitative study among older adults participating in a prevention trial

Abstract: Background: A better insight into older adults' understanding of and attitude towards cognitive disorders and their prevention, as well as expectations and reasons for participation in prevention trials, would help design, conduct, and implement effective preventive interventions. This qualitative study aimed at exploring the knowledge and perceptions of cognitive disorders and their prevention among participants in a prevention trial. Methods: Semi-structured interviews were conducted among the participants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…These ndings generally align with the existing literature: for example maintaining independence (50) and enjoyment of activities (51) seem key motivators amongst this group. We also found that an awareness of, and desire to avoid, the consequences of dementia seemed to motivate cognition-protective behaviours (52), whilst other health conditions arose as a possible barrier. Additionally, our ndings extend understandings about the value of social support.…”
Section: Discussionmentioning
confidence: 69%
“…These ndings generally align with the existing literature: for example maintaining independence (50) and enjoyment of activities (51) seem key motivators amongst this group. We also found that an awareness of, and desire to avoid, the consequences of dementia seemed to motivate cognition-protective behaviours (52), whilst other health conditions arose as a possible barrier. Additionally, our ndings extend understandings about the value of social support.…”
Section: Discussionmentioning
confidence: 69%
“…These findings generally align with the existing literature: for example, maintaining independence [ 64 ] and enjoyment of activities [ 65 ] seem key motivators amongst this group. We also found that an awareness of, and desire to avoid, the consequences of dementia seemed to motivate cognition-protective behaviours [ 71 ], whilst other health conditions arose as a possible barrier. Additionally, our findings extend understandings about the value of social support.…”
Section: Discussionmentioning
confidence: 99%
“…In highly educated and developed countries, cognitive impairments are known as an unavoidable part of normal aging. This increases fear and anxiety in individuals, feelings of hopelessness, and stigmatization (26). In the less developed countries, people accept patients with AD more easily and stigmatize them less (25).…”
Section: Discussionmentioning
confidence: 99%